Challenges to teacher education in difficult economic times : international perspectives - Stephenson, Joan; Ling, Lorraine (London : Routledge, Taylor & Francis Group, 2014)
'Teacher education in a financial crisis - what are the consequences and how can probity be maintained? Education, like most other parts of everyday life, is experiencing the challenges brought about by global financial constrictions. This book presents the experiences and views of practising teacher educators from multiple countries and continents on how the melt-down in world economics has affected and will continue to affect teacher education and concomitant experiences in schooling. The ramifications are seen to extend into every aspect of teacher preparation, continuing staff development and teacher support, and there are significant implications for the quality of teaching and learning, and the ethos and standing of the process of education as a whole. Drawing on educational theory and social, political, and economic discourses, the book addresses issues such as policy, philosophy, organisation, funding, resources, modes of teaching and learning, curricular change, recruitment and retention, amongst others, and provides a snap-shot across diverse contexts. It aims to provide an evaluative, analytical but reflective picture of teacher education in the light of the world economic crisis, whilst exploring good practice and suggesting future strategies to develop the quality of teacher education and professional support, teaching and learning. The volume provides an insight into the need for a new paradigm for teacher education: one that involves teacher educators in devising a discourse of positive and radical change. It will be a valuable resource for teacher educators, educational leaders, policy makers, educational commentators and teachers seeking to engage with the scholarship of teaching as a means to engage in continuous professional development'--
Keywords: Teachers -- Training of -- Economic aspects -- Cross-cultural studies